PENGARUH PROFIL KEMAMPUAN MEMBUAT KEPUTUSAN PADA MAHASISWA BIOLOGI UNIVERSITAS TANJUNGPURA - Baiq Zulfa Rahmi; Afandi Afandi; Titin Titin (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
Making a decision is taking action after considering and analyzing the problem. Having the ability to make decisions is an action that needs to be trained, especially for biology teacher students so that they can solve problems by choosing important steps in understanding difficult decision situations. The purpose of this study was to analyze the decision-making ability of Biology Education students at Tanjungpura University, Pontianak. The type of research used is descriptive qualitative with a survey study method and a random sample approach. The results of the study indicate that overall the profile of decision-making skills possessed by students is in the high category based on the 9 decision-making ability profiles presented, including the ability to understand future dangers associated with actions. This study is believed to be a stepping stone to improving decision-making skills and creativity that can produce more than just making new choices. Furthermore, further research is needed to deepen the indicators of the decision- making ability profile in students. Furthermore, further research is needed to deepen the indicators of the decision-making ability profile in students.